ANALYSIS OF THE APPLICATION OF THE SINGLE SUBMISSION SYSTEM (SSM) ON THE EFFECTIVENESS OF FOREIGN CONTAINER SHIP CLEARANCE AT PT JASA CENTINA SENTOSA TANJUNG PERAK SURABAYA - Putri, Priyadika Hastari; Setyawan, Suprihono; Hanik, Kumila (International Journal of Management, Business, and Social Sciences, 2024)
This study aims to analyze the effect of the Single Submission System (SSM) implementation on the effectiveness of clearance in and out activities of foreign container ships at PT Jasa Centina Sentosa at Tanjung Perak Port, Surabaya. The research method used is a combination (mixed methods) with a sequential explanatory design. Primary data were obtained through surveys and interviews with employees of PT Jasa Centina Sentosa, with a sample of 30 respondents. The independent variable in this study is the implementation of the Single Submission System (SSM) of the carrier, while the dependent variable is the effectiveness of the ship clearance process. Data were analyzed using simple linear regression. The results of the analysis show that the implementation of the Single Submission System (SSM) has a positive and significant effect on the effectiveness of the ship clearance process. The more optimal the implementation of SSM, the more effective the clearance in and out activities of foreign container ships at the port. This study also identified several obstacles that can hinder the implementation of SSM, such as less than optimal coordination between agencies and lack of education for system users